Iodine‐ion‐induced Size‐tunable Co3O4 Nanowires and the Size‐dependent Catalytic Performance for CO Oxidation. Issue 12 (10th September 2013) - Li, Yaguang; Zhu, Liping; Guo, Yanmin; Jiang, Jie; Hu, Liang; Wen, Zhen; Sun, Luwei; Ye, Zhizhen
<x xml:space="preserve">Abstract</x> Pick on someone your own size: Size‐tunable Co3O4 nanowires, prepared through an iodine‐ion‐mediated hydrothermal synthesis, were found to be excellent catalysts for CO oxidation. By controlling the dimensions of the nanowires the catalytic activity for CO oxidation could be tuned.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>